Analisis Penguatan Dinas Perhubungan Dalam Pengawasan Perizinan Angkutan Kota Di Kota Medan - Ahmad Fikhri (Inovasi Pratama Internasional. Ltd, 2022)
The Medan City Transportation Service is the implementing element of the Medan City Government in the field of transportation, having duties in the field of public transportation services. City transportation is one of the modes of transportation that is still the focus of improving the government and public transportation service providers. The problems studied are how to regulate the mechanism for controlling urban transportation licensing in the city of Medan and how the supervision of the Department of Transportation on the licensing of city transportation in the city of Medan. The research conducted is empirical research, namely by conducting interviews. The data collection method in this research is library research and field research. The data analysis used is qualitative data. The legal regulation of urban transportation in Medan City is Law no. 22 of 2009 concerning LLAJ and Medan City Regulation No. 2 of 2014 concerning Regional Levies in the Field of Transportation and Perwal of Medan City No. 41 of 2018 concerning Delegation of Partial Licensing and Non-Licensing Authorities to the Head of the Medan City Investment and One-Stop Integrated Service Office. Supervision of the Department of Transportation on city transportation permits in the city of Medan is carried out in two ways, namely: internal supervision and external supervision. In carrying out the task of supervising and controlling transportation in the city of Medan, the Medan City Transportation Service coordinates with the Traffic Traffic Unit 2 (two) times a year, namely in June and November.